Correlation of the palmar pressure strength and nutritional state in elderly practitioners of physical activity (Research, Society and Development, 2021)
The present study aimed to assess handgrip strength, nutritional status and its relationship with functional limitations in the elderly. A cross-sectional, quantitative study with a sample of 60 elderly women> 60 years old, carried out at the Centro de Convivência Dos Idosos, located in the city of Northeast Brazilian. Variables were studied to assess body composition. Food consumption was assessed using the Food Frequency Questionnaire (FFQ) adapted for the elderly. The Palmar Grip Force (FPP) data were evaluated using the formula. For significant differences, p